Pengaruh kadar air dalam kulit terhadap kuat rekatan lem - Sofyan Karani; Suhadijono Suhadijono (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1991)
The objective of the research is to know the influence of Moisture in the leather to adhesive resistance of glue. The glue used is Aica Aibon, Herferin, Striot 275 and Rokoll Prima DX by dry air, subn light and dryong oven treatmrnt. The result od research the moisture in the leather up to 20% won’t influence the adhesive resistance of the glue, but it will influence the drying time of glue. Adhesive resistance optimum for 4 kinds of glue are between 0.427 0.568 kp/cm2 by pressuring 3 kg/cm2 and pressuring time 15 second